The Effect Of Work-Life and Social Media Balances On Moslem Family Teachers In Pandemic Time - Anizar Rahayu; Abdul Rahman Shaleh; Rosleny Marliani (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Distance learning demands extra work and adjustment of teachers in doing a task to educate their students. This condition causes a conflict such as interfering with wholeness that leads to family resilience conflict. In Islamic teaching, family resilience can be achieved by living the principles of zawaj (pair), mitsaqan-ghaliza (solid bond), musyaran (good association), and musyawarah (mutual agreement) in relationship between family members. The study aimed to find out the effect of work-life and social media balances on teachers' families' resilience and was measured by Islamic family resilience values. The participants were 161 teachers aged 21-36 years in Cikarang area of Bekasi Regency who used social media. Data was taken through Google-form with three scales, namely Islamic Family Resilience which was developed by Islamic family resilience aspect of BP4 called IMRS®, the scale of work balance was from Fisher, Bulger, & Smith (2009), and the scale of social media balance was from Kumar & Priyadarshini (2018). Data was taken by a nonprobability sampling with purposive sampling technique. The data were analyzed with multiple regression analysis. The results showed that the variables of work-life and social media balances had a significant effect on family resilience. The study also showed that three dimensions had a significant effect, namely (2) the mixing of person to work, (3) enrichment of personal life from work, and (6) the use of social media for personal. This study implied that the importance of understanding family members related to the fulfillment of common goals and must be communicated.